OPTIMIZING MATERNAL AND CHILD HEALTH: ENHANCING PUBLIC AWARENESS OF TORCH INFECTIONS DURING PREGNANCY - Ekaputri, Tia Wida; Enis, Rina Nofri; Tarawifa, Susan; Harahap, Huntari; Syauqy, Ahmad; Perkasa, Tengku Arief Buana (Medical Dedication (medic) : Jurnal Pengabdian kepada Masyarakat FKIK UNJA, 2025)
TORCH infections (Toxoplasmosis, Rubella, Cytomegalovirus, Herpes simplex) pose significant risks during pregnancy, contributing to congenital abnormalities and adverse neonatal outcomes. In Indonesia, limited public awareness and inadequate preventive practices exacerbate these risks. This community service initiative aimed to enhance knowledge about TORCH infections among reproductive-aged women through a hybrid educational seminar. Conducted in collaboration with Peduli TORCH, the program utilized the "5P Framework" (Pathogen Awareness, Prenatal Screening, Pathogen Management, Postnatal Monitoring, Preventive Practices) to deliver evidence-based strategies. A total of 54 participants (87% female, 61.1% from Jambi Province) attended the seminar, combining in-person and virtual engagement. Pre- and post-tests assessed knowledge improvement, revealing a statistically significant median score increase from 70.0 to 100.0 (p<0.001, Wilcoxon test). Participants reported high satisfaction with the seminar’s content, interactive format, and accessibility, though logistical refinements were suggested for future iterations. The initiative successfully bridged knowledge gaps, emphasizing the importance of early screening, vaccination, and hygiene practices. By empowering women and leveraging community engagement, this program highlights the potential of targeted educational interventions to reduce TORCH-related morbidity and improve maternal-child health outcomes. Culturally adapted, hybrid approaches demonstrate promise for scalable public health strategies in low-resource settings.